2018
DOI: 10.1177/1035304618782558
|View full text |Cite
|
Sign up to set email alerts
|

Singapore’s restructuring of low-wage work: Have cleaning job conditions improved?

Abstract: Singapore’s Progressive Wage Model, introduced in 2012 and mandatory in the cleaning industry since 2015, is a skills- and productivity-based approach to redesigning jobs and restructuring wages in the largely outsourced cleaning, security and landscaping sectors. Focusing on cleaning work in the food and beverage industry, this case study examines some early outcomes of this national drive to reduce wage inequality by improving the pay and conditions of commodified work in a sector subject to outsourcing-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Ng et al (2018) studied the outcomes of Singapore’s Progressive Wage Model that was mandated in the cleaning industry in 2015. The authors found that there were some improvements in wages and conditions particularly in the areas of paid sick leave, vacation leave, health benefits, transport allowances and meals for restaurant workers.…”
Section: What We Know About Minimum Wages?mentioning
confidence: 99%
See 1 more Smart Citation
“…Ng et al (2018) studied the outcomes of Singapore’s Progressive Wage Model that was mandated in the cleaning industry in 2015. The authors found that there were some improvements in wages and conditions particularly in the areas of paid sick leave, vacation leave, health benefits, transport allowances and meals for restaurant workers.…”
Section: What We Know About Minimum Wages?mentioning
confidence: 99%
“…Nonetheless, low-paid cleaners were still subject to certain vulnerabilities. These vulnerabilities, as Ng et al (2018) pointed out, were often structural problems within the workplace environment, and therefore, eroded the potential benefits of having minimum wages set at living wage levels. In many cases, workers were unaware of the benefits, and employers violated employee rights.…”
Section: What We Know About Minimum Wages?mentioning
confidence: 99%
“…They have had great success in demonstrating their IR policy-influence to members. This appears to contrast not just with the more positive, collaborative agendas of leading corporations and associations in Western European countries, for example on climate change transitions (European Round Table of Industrialists, 2018), but with how, for example, the Singapore National Employers' Federation has collaborated with government and unions in trying to reduce pay inequality by improving pay and conditions in low-pay sectors (Ng et al, 2018). At the same time, Australia's major associations' policy successes have produced an oppositional environment that threatens some successes.…”
Section: The Socio-political Context For Pro-employer Interest Lobbying and Publicitymentioning
confidence: 95%
“…With rapid economic growth that propelled it from a poor developing country to one of the richest and most industrialised countries in the world in merely three decades (Ng, 2013 ), Singapore has experienced acutely the various duality-inducing developments outlined in the previous section. As a highly globalised economy, many of the technological adoption, performance management, and cost reduction practices are often promptly adopted (Bali et al, 2019 ; Ng et al, 2018 ; Stanton & Nankervis, 2011 ; Teo, 2007 ; Wan, 2003 ). From a small trading post, Singapore’s rapid economic growth began with labour-intensive manufacturing in the 1960s and 1970s (Chiu et al, 1997 ; Pang & Lim, 2015 ).…”
Section: Pandemic Disruption In a Polarised Labour Marketmentioning
confidence: 99%